Understanding non-permanent mobility: Factors influencing resident movement in Racang Welak Village, Welak Subdistrict, West Manggarai Regency - Afat, Gordianus; Jamil, Achmad Maulana Malik; Kusufa, Roni Alim Ba’diya (Journal of Placemaking and Streetscape Design, 2024)
Background: The factors of mobility in this study refer to the push and pull factors influencing the non-permanent mobility of the residents of Racang Welak Village, Welak Subdistrict, West Manggarai Regency. Most of the residents in Racang Welak Village are seasonal farmers. Non-permanent mobility is influenced by good accessibility and sufficient access to technology. The area of Racang Welak Village cannot fully meet the needs of the local community, leading them to seek employment outside their area despite the strategic potential of Racang Welak to boost their economy. Method: The objectives of this study are to identify the factors that cause the residents of Racang Welak Village, Welak Subdistrict, West Manggarai Regency, to engage in non-permanent mobility. This research is a descriptive qualitative study. Data collection methods include observation, interviews, and documentation. The sample consists of residents of Racang Welak Village who participate in non-permanent mobility. Result: The results of this study show that the fertile soil conditions in Racang Welak Village allow for the cultivation of various types of crops, resulting in many residents working as seasonal farmers. Seasonal farmers whose needs are not met locally often seek information about job opportunities elsewhere. With information received from family members in the destination area, the residents of Racang Welak Village decide to work in other regions without the initial intention to settle there. Conclusion: The push factors for non-permanent mobility among Racang Welak residents include unmet needs in their home area. Despite having to bear transportation costs, they still choose to engage in non-permanent mobility. The pull factors include a pleasant environment, good social interactions, and job opportunities obtained through relatives in the destination area. Additionally, the work locations are strategic and offer jobs that match their professional skills, resulting in higher incomes. Novelty/Originality of this study: This research aims to identify the push and pull factors of non-permanent mobility and how the inability to meet local needs drives residents to seek employment outside the region. These findings apply to designing local economic development policies that can reduce dependence on non-permanent mobility by increasing job opportunities and accessibility in the region of origin.